Penerapan Terapi Musik Suara Alam dan Aromaterapi Chamomile Terhadap Mual Muntah dan Kecemasan Pasien Gastritis - Lie Liana Fuadiati; Desy Rinawaty; Afiatur Rohimah (Malahayati Nursing Journal, 2026)
ABSTRACT Gastritis is a disease that can affect all levels of society, most commonly affecting those of productive age. People in productive age are vulnerable to infection due to busy schedules, a lifestyle that doesn't pay attention to health, and the stress they experience. Gastritis can recur, and relapses are influenced by poor diet and stress factors.Analyzing the application of natural sound music therapy and chamomile aromatherapy on nausea, vomiting and anxiety in gastritis patients. This study used a Quasi-Experimental Pre-Post Test with One Group Design. The sample in this study were 36 gastritis patients. The research instrument was the DASS 42 (Depression Anxiety Stress Scale) questionnaire to measure anxiety consisting of 14 questions, and nausea and vomiting were measured using a nausea and vomiting questionnaire consisting of 3 questions. Data analysis in this study used the Wilcoxon Test statistical test. Nausea and vomiting of respondents before the intervention were mostly moderate, as many as 21 respondents (58.3%). And nausea and vomiting of respondents after the intervention were mostly mild, as many as 15 respondents (41.6%). Anxiety of respondents before the intervention was mostly moderate, as many as 12 respondents (33.33%). And anxiety of respondents after the intervention Most had mild anxiety, as many as 16 respondents (44.44%). The results of the Wilcoxon test of nausea and vomiting in gastritis patients after natural sound music therapy and chamomile aromatherapy showed that Sig. was 0.000 or 0.05. The results of the Wilcoxon test of anxiety in gastritis patients after natural sound music therapy and chamomile aromatherapy showed that Sig. was 0.000 or 0.05. The application of natural sound music therapy and chamomile aromatherapy has been shown to have an effect on nausea, vomiting, and anxiety in gastritis patients. Classical music plays a crucial role in relieving mental tension and neutralizing emotions. By utilizing a regular tempo, rhythm, melody, and harmony, classical music can stimulate alpha and beta waves in the brain, providing a relaxing and calming effect. Aromatherapy affects the nervous system. When inhaled, aromatherapy stimulates the olfactory nerve and is transmitted to the hypothalamus, which then triggers the release of chemicals in the brain that have a calming and relaxing effect. Keywords: Nature Music, Aromatherapy, Nausea and Vomiting, Anxiety  ABSTRAK Gastritis merupakan penyakit yang dapat menyerang semua kalangan Masyarakat, paling banyak menyerang usia produktif. Di usia produktif masyarakat rentan terserang karena tingkat kesibukan, gaya hidup yang kurang memperhatikan kesehatan serta stres yang mudah dialami. Gastritis dapat mengalami kekambuhan dimana kekambuhan terjadi dipengaruhi oleh pola makan yang tidak baik dan faktor stress. Menganalisis penerapan terapi musik suara alam dan aromaterapi chamomile terhadap mual muntah dan kecemasan pasien gastritis. Desain penelitian ini menggunakan Quasi Experimental Pre Post Test with One Group Design. Sampel pada penelitian ini adalah 36 pasien gastritis. Instrumen penelitian ini yaitu Kuesioner DASS 42 (Depression Anxiety, Stres Scale) untuk mengukur kecemasan terdiri dari 14 pertanyaan dan mual muntah diukur dengan kuesioner mual muntah terdiri dari 3 pertanyaan. Analisis data pada penelitian ini menggunakan uji statistik Wilcoxon Test. Mual muntah responden sebelum intevensi sebagian besar sedang sebanyak 21 responden (58,3%). Dan mual muntah responden sesudah intevensi sebagian besar ringan sebanyak 15 responden (41,6%). Kecemasan responden sebelum intevensi sebagian besar memiliki kecemasan sedang sebanyak 12 responden (33,33%). Dan kecemasan responden sesudah intevensi Sebagian besar memiliki kecemasan ringan sebanyak 16 responden (44,44%). Hasil Uji Wilcoxon mual muntah pada pasien gastritis sesudah terapi musik suara alam dan aromaterapi chamomile menunjukkan bahwa Sig. sebesar 0,000 atau 0,05. Hasil Uji Wilcoxon kecemasan pada pasien gastritis sesudah terapi musik suara alam dan aromaterapi chamomile menunjukkan bahwa Sig. sebesar 0,000 atau 0,05. Terdapat pengaruh penerapan terapi musik suara alam dan aromaterapi chamomile terhadap mual muntah dan kecemasan pasien gastritis. Musik  klasik  memiliki  peran penting dalam meredakan  ketegangan pikiran dan menetralkan emosi. Dengan  memanfaatkan tempo, ritme, melodi, dan harmoniyang teratur, musik klasik mampu merangsang  gelombang  alfa  dan  beta  pada  otak,  memberikan efek  rileks  dan  ketenangan. Aromaterapi berpengaruh pada sistem saraf. Saat dihirup, aromaterapi merangsang saraf penciuman (olfactory nerve) dan diteruskan ke hipotalamus, yang kemudian memicu pelepasan zat kimia di otak yang memberikan efek tenang dan rileks. Kata Kunci: Musik Alam, Aromaterapi, Mual Muntah, Kecemasan.